NILAI MORAL DAN NILAI BUDAYA DALAM NOVEL KELOPAK CINTA KELABU KARYA SUHAIRI RACHMAD DAN IMPLIKASINYA DALAM PEMBELAJARAN APRESIASI SASTRA DI SMP - Emi Emi (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2017)
This study aims to describe and understand how the novel analysis in expressing the moral values and cultural values contained in Novel Kelabak Cinta Kelabu Karya Suhairi Rachmad. The method used in this research is descriptive qualitative method intended to obtain a picture of moral values and cultural values contained in the novel Kelopak Cinta Kelabu by Suhairi Rachmad. The data collected by way of documentation, then recorded in the paper work based on the moral values and cultural values contained in the novel, then analyzed based on the theory presented Nurgiyantoro and Ibn Miskawayh while cultural values are analyzed with the category of cultural values of koentjaningrat. The conclusion of this study is the entire category of moral values based on the theory presented by Ibn Miskawayh is contained in the novel Kelabak Cinta Kelabu by Suhairi Rachmad. While the category of cultural values based on the theory presented by Koentjaningrat entirely contained in the novel Kelabak Cinta Kelabu by Suhairi Rachmad. Implication of moral values and cultural values in the novel Kelopak Cinta Kelabu by Suhairi Rachmad can be implicated as a literary appreciation material in SMP class IX semester II.